Author Correction: Effects of influent COD/N ratios on nitrous oxide emission in a sequencing biofilm batch reactor for simultaneous nitrogen and phosphorus removal. Issue 1 (December 2018) - Ge, Guanghuan; Zhao, Jianqiang; Li, Xiaoling; Ding, Xiaoqian; Chen, Aixia; Chen, Ying; Hu, Bo; Wang, Sha
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.